The Lang strain of reovirus serotype 1 and the Dearing strain of reovirus serotype 3 differ in their sensitivities to beta interferon. - Jacobs, B L (1991)
Replication of the Dearing strain of reovirus serotype 3 in mouse L cells was decreased 17- to 100-fold when a saturating dose of beta interferon (1,000 IU/ml) was used. Replication of the Lang strain of reovirus serotype 1 was inhibited only two- to threefold under similar conditions. It therefore appears that closely related strains of reovirus differ in their sensitivities to beta interferon treatment of mouse L cells.